Recommendations by the scientific department of neuroimmunology of the Brazilian Academy of Neurology (DCNI/ABN) and the Brazilian Committee for treatment and research in multiple sclerosis and neuroimmunological diseases (BCTRIMS) on vaccination in general and specifically against SARS-CoV-2 for patients with demyelinating diseases of the central nervous system - Becker, Jefferson; Campos Ferreira, Lis; Damasceno, Alfredo; Bichuetti, Denis Bernardi; Christo, Paulo Pereira; Callegaro, Dagoberto; Lana Peixoto, Marco Aurélio; De Carvalho Sousa, Nise Alessandra; De Almeida, Sérgio Monteiro; Adoni, Tarso; Santiago-Amaral, Juliana; Junqueira, Thiago; et al. (FapUNIFESP (SciELO), 2021)
The Scientific Department of Neuroimmunology of the Brazilian Academy of Neurology (DCNI/ABN) and Brazilian Committee for Treatment and Research in Multiple Sclerosis and Neuroimmunological Diseases (BCTRIMS) provide recommendations in this document for vaccination of the population with demyelinating diseases of the central nervous system (CNS) against infections in general and against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19. We emphasize the seriousness of the current situation in view of the spread of COVID-19 in our country. Therefore, reference guides on vaccination for clinicians, patients, and public health authorities are particularly important to prevent some infectious diseases. The DCNI/ABN and BCTRIMS recommend that patients with CNS demyelinating diseases (e.g., MS and NMOSD) be continually monitored for updates to their vaccination schedule, especially at the beginning or before a change in treatment with a disease modifying drug (DMD). It is also important to note that vaccines are safe, and physicians should encourage their use in all patients. Clearly, special care should be taken when live attenuated viruses are involved. Finally, it is important for physicians to verify which DMD the patient is receiving and when the last dose was taken, as each drug may affect the induction of immune response differently.
Recomendações do Departamento Científico de Neuroimunologia da Academia Brasileira de Neurologia (DCNI/ABN) e do Comitê Brasileiro de Tratamento e Pesquisa em Esclerose Múltipla e Doenças Neuroimunológicas (BCTRIMS) sobre vacinação em geral e contra a SARS-CoV-2 para pacientes com doenças desmielinizantes do sistema nervoso central
Keywords: Demyelinating Autoimmune Diseases, CNS; Multiple Sclerosis; Neuromyelitis Optica; SARS-CoV-2; Vaccination; COVID-19